2008
DOI: 10.1593/neo.07817
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1-Mediated Expression and Secretion of Kallikrein 6 in Colon Cancer Cells

Abstract: Kallikreins are secreted proteases that may play a functional role and/or serve as a serum biomarker for the presence or progression of certain types of cancers. Kallikrein 6 (KLK6) has been shown to be upregulated in several types of cancers, including colon. The aims of this study were to elucidate pathways that influence KLK6 gene expression and KLK6 protein secretion in the HCT116 human colon cancer cells. Our data indicate a central role for caveolin-1 (CAV-1), the main structural protein of caveolae, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 34 publications
1
33
0
1
Order By: Relevance
“…Furthermore, Klucky et al, 2007 trying to explain the function of KLK6 in cancer, provided evidence that KLK6 induces E-cadherin shedding and thus, promotes cell proliferation, migration, and invasion. In addition, recent data presented by Henkhaus et al (2008b) indicate a central role for caveolin-1, the main structural protein of caveolae in both KLK6 gene expression and protein secretion of colon cancer cell line HCT116.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, Klucky et al, 2007 trying to explain the function of KLK6 in cancer, provided evidence that KLK6 induces E-cadherin shedding and thus, promotes cell proliferation, migration, and invasion. In addition, recent data presented by Henkhaus et al (2008b) indicate a central role for caveolin-1, the main structural protein of caveolae in both KLK6 gene expression and protein secretion of colon cancer cell line HCT116.…”
Section: Discussionmentioning
confidence: 89%
“…Follow-up clinical studies on cancer tissues suggest a potential value of KLKs 6 and 10 as prognostic indicators of the disease, because their dysregulation pattern was correlated with advanced disease stages (10,31 ). Recently, caveolin-1, the primary structural protein of caveolae, has been implicated in the aberrant expression of KLK6 in colon cancer (32 ). Whether any of the other KLKs have clinical potential as biomarkers requires further elucidation.…”
Section: Gastrointestinal Cancers Colorectal Cancermentioning
confidence: 99%
“…These genes are expressed as single-chain preproenzymes of approximately [30][31][32][33][34][35][36][37][38][39][40]. Thus far, the crystal structures of the mature KLK1, KLK3, KLK4, KLK5-7, and pro-KLK6 proteins have been determined and shown to be highly similar (4 -6 ).…”
mentioning
confidence: 99%
“…Recently, it has also been reported that PP2A was targeted to caveolae of cardimyocyes [18]. Incase of HCT116 (colon cancer) cells and over expression of Caveolin-1 was found to increase the amount of phosphorylated Akt by inhibiting the activity of Akt-negative regulators PP1 and PP2A [19]. In view of the association between PP2A and Caveolin-1, we examined the distribution of Caveolin-1 and PP2A.…”
Section: Resultsmentioning
confidence: 96%